Brand Naming Practices Of Chinese Enterprises: A Tentative Model - Wai, sum Siu; Zhang, Yi (Asian Academy of Management (AAM), 2000)
Literature review suggests that Western researchers adopt the stepwise approach to investigate the brand naming process and develop models and tenets for brand naming practices. Notably, however, management researchers query the applicability of the broad Western brand naming principles in a Chinese sociocultural context. This paper examines the brand naming practices of Chinese enterprises. Eleven Chinese managers were in-depth interviewed. The research results reveal that Chinese managers tend to follow a four-step approach in choosing brand names. They are: 1) generating brand names, 2) screening brand names, 3) choosing brand names, and 4) applying for registration. Chinese managers tend to use ‘good luck’ and ‘foreign-sounding’ frequently to evaluate brand names. Advertising agencies and brand consultants are involved in the evaluation process. Interestingly, government officials are influential in the brand naming decision of Chinese enterprises. However, few enterprises undertake formal research such as consumer surveys to evaluate brand names. Most Chinese enterprises, to play safe, register for more than one brand name to establish a name pool. The research findings suggest that the Eastern and Western brand naming processes are different and there is a need to develop a Chinese brand naming model.